Problems of State Regulation of Innovation Policy in the Russian Federation and Foreign Countries - PAVLOV, Aleksandr Jurievich; BATOVA, Vera Nikolaevna; Kovalyova, Natalia Nikolaevna; KOLESNIKOV, Andrey Vladimirovich; SOKOLOV, Alexander Yurevich; SOBOLEVA, Yulia Viktorovna (Journal of Advanced Research in Law and Economics, 2017)
In modern conditions of nanotechnology, information and other emerging technologies are important factors for sustainable innovative economic development. Innovative development of economy forms the basis of a dynamic, high-quality growth of the national economy, changing its structural characteristics, and defines its international competitiveness and overall vitality. However, the decisive turn to innovation model of development through the intensive use of the latest techniques and technologies, pioneer and major inventions, at the same time creates the preconditions for the destabilization of the economy and a source of specific threats to economic security. Safe development of nano-industry is an urgent task that promotes the positive dynamics of innovation development for the long term. You must carefully balance the potential risks and benefits of nanotechnology, securing at the normative level, the basic principles of precaution ‘, thereby establishing an objective model of innovation-legal policy in the territory of the State, taking into account the impact of international standards on its formation and continued operation. Establishment of information, its collection, processing, accumulation, storage, retrieval, dissemination and provision of the consumer, the creation and use of information technology and facilities, data protection and the rights of entities involved in information processes, cannot take place without the participation of the State. Informatization as the process irreversible and unavoidable, is for States to ensure the State of protection of the interests of citizens, society and State, as well as create conditions for qualitative and effective provision for citizens, public authorities and local self-government bodies, organizations, public associations, to develop federal and regional information systems and networks, to ensure their compatibility and interaction in a single information space of the Russian Federation. Given the speed of development in this area, it should be recognized that the legal, organizational and technology information sphere is the least protected part of the State. Formation of an effective system of legal support in the development and application of innovative technologies is a key objective of national development strategies nanotechnology industry, information and other innovative processes in the context of globalization of markets. The paper summarizes the features of state regulation of innovation development in foreign countries in terms of providing legal regulation. Russian analyzed problems of legal regulation of nanotechnologies, conceptual directions of formation of innovation policy in Russia.